LATEX : A document preparation system : User's guide and reference manual - Leslie Lamport
LaTex is a software system for typesetting documents. Because it is especially good for technical documents and is available for almost any computer system, LaTex has become a lingua franca of the scientific world. Researchers, educators, and students in universities, as well as scientists in industry, use LaTex to produce professionally formatted papers, proposals, and books. They also use LaTex input to